(untitled) (International Journal of Physiotherapy, 2022)
Abstract: Healthy individuals can maintain static and dynamic balance via appropriate allocation among proprioceptive (Pro), vestibular (Ve), and visual sensory systems, established as the dynamic systems theory (DST). However, people living with the human immunodeficiency virus (PLHIV) underperform one or more of these systems, altering their ability to control balance. The issue is to determine specific balance system deficits in PLHIV during many challenging standing tasks to understand better where these deficiencies are located. The study aims to distinguish balance deficits in PLHIV using challenging activities with a reduced base of support. Methods: Thirty adults living with HIV from La Perla Gran de Precio Community Center took part in this examination. We collected balance kinematics with accelerometers and gyroscopes during five balancing tasks. The five tasks included balancing on a firm surface with double limb support (DLS) and single limb support (SLS) and balancing tasks on an unstable surface (foam) with vertical head movements at 60 bpm set by a metronome. Results: The balancing tasks requiring shifts from SL to DL on firm and foam surfaces with visual input alterations (eyes closed and open) and head movements showed significant increases in sway (p<0.001). The medial-lateral (ML) and anterior-posterior (AP) sway velocities displayed substantial increases (p<0.001) in AP sway among all five tasks and a considerable decrease in ML among the five tasks. Conclusion: People living with HIV have balance instability, with increased difficulty during conditions requiring to bear weight on a single limb with Ve and Pro adaptations. The mechanism creating these deficits in the Ve and Pro systems is yet unsettled. Future studies should focus on 1) early assessment of Ve and Pro, 2) the mechanisms affecting said balance systems, and 3) the correlation of ART medications with balance and fall risk in this population.